Some new methods of indirect determination of metals based on adsorption and complexation properties of Arsenazo III azo dye - Komersová, Alena; Bartoš, Martin; Kalcher, Kurt; Vytřas, Karel (Univerzita Pardubice, 1997)
Voltammetric properties of Arsenazo III were studied in view of its exploitation for trace analysis of metal ions using adsorptive stripping voltammetry. Conditions for determinations of uranium and aluminium were optimized and the corresponding procedures suggested.